The concept of professional identity: Kindergarten teachers’ professionalism requirement in Malaysian preschool curriculum - Abdul Halim Masnan; Muhammad Haziq Mohd Sharif; Masayu Dzainuddin; Mohd Mokhzani Ibrahim; Asmayati Yahaya; Che Nidzam Che Ahmad; Hafsah Taha; Saipolbarin Ramli; Rosfizah Md Taib; Saedah Siraj; Mazlina Che Mustafa (International Journal of Evaluation and Research in Education (IJERE), 2021)
This study aimed to determine the professional identity concept based on professionalism requirement in Malaysia’s new preschool curriculum. Three professional identities identified through works of literature such as professional qualifications, experience and professional development were verified based on the constructed hypothesis to validate the concept of professional identity. The analysis findings showed a significant difference between professional qualifications. The same analysis, however, demonstrated that there was no significant difference on the preschool curriculum knowledge with regards to experience, but there was a significant indication of interaction between professional qualifications and experience on preschool curriculum knowledge. Meanwhile, for the one-way ANOVA test, there was a significant difference in the preschool curriculum knowledge based on professional development. The findings of this study confirmed that professional knowledge and professional development respectively hold a direct impact on the preschool curriculum, while experience acts as a support for professional qualifications.